2015
DOI: 10.1523/jneurosci.5051-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

GIRK Channels Modulate Opioid-Induced Motor Activity in a Cell Type- and Subunit-Dependent Manner

Abstract: G-protein-gated inwardly rectifying Kϩ (GIRK/Kir3) channel activation underlies key physiological effects of opioids, including analgesia and dependence. GIRK channel activation has also been implicated in the opioid-induced inhibition of midbrain GABA neurons and consequent disinhibition of dopamine (DA) neurons in the ventral tegmental area (VTA). Drug-induced disinhibition of VTA DA neurons has been linked to reward-related behaviors and underlies opioid-induced motor activation. Here, we demonstrate that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 78 publications
1
63
0
Order By: Relevance
“…We recently demonstrated that VTA DA neurons in DATCre(+):Girk2 flox/flox mice (GIRK2 DA KO mice) exhibited diminished inhibitory somatodendritic current responses to GABA B R activation (Kotecki et al, 2015). To test whether autoreceptor-mediated signaling in VTA DA neurons from GIRK2 DA KO mice was similarly blunted, we measured currents evoked by a saturating concentration (20 μM) of the D 2/3 R agonist quinpirole.…”
Section: Results D 2/3 R-dependent Signaling and Excitability In Vtamentioning
confidence: 99%
See 4 more Smart Citations
“…We recently demonstrated that VTA DA neurons in DATCre(+):Girk2 flox/flox mice (GIRK2 DA KO mice) exhibited diminished inhibitory somatodendritic current responses to GABA B R activation (Kotecki et al, 2015). To test whether autoreceptor-mediated signaling in VTA DA neurons from GIRK2 DA KO mice was similarly blunted, we measured currents evoked by a saturating concentration (20 μM) of the D 2/3 R agonist quinpirole.…”
Section: Results D 2/3 R-dependent Signaling and Excitability In Vtamentioning
confidence: 99%
“…The generation of Girk2 flox/flox , DATCre(+/ − ):Girk2 flox/flox , and Pitx3-eGFP(+)/DATCre(+/ − ):Girk2 flox/flox mice was described previously (Kotecki et al, 2015). DATCre (B6.SJLSlc6a3 tm1.1(cre)Bkmn ) and Drd1a-tdTomato (B6.Cg-Tg(Drd1a-tdTomato)6Calak/J) lines were purchased from The Jackson Laboratory (Bar Harbor, ME), and the Drd2-eGFP strain (Tg (Drd2-EGFP)S118Gsat) was obtained from the Mutant Mouse Regional Resource Center.…”
Section: Animalsmentioning
confidence: 99%
See 3 more Smart Citations